JAD-CASE : Tasks and documents specification for requirements engineering process - Balda, María Verónica (1997)
The structured techniques for systems analysis and design are still the most widely known. One of the alternatives of this technique is the JAD methodology (Joint Application Design). This methodology is an improvement with respect to the existing ones - such as classical life cycle, spiral development, increasing prototypes - since it expands the role of the users, and allows them to define their own objectives, requirements and external design. Problem definition, as well as requirements initial analysis, are the basis for the whole software engineering process; the success of the developed system depending mostly on these two initial stages. This is the reason why the use of a methodology emphasizing these initial stages is important, since it would provide a higher quality design, easy to maintain and modify. The proposed objective was the construction of a CASE tool which would include the JAD methodology within an environment where participants (users and analysts) can interact to manage the flow of tasks and documents generated in the Requirements Engineering stage.